Identification of the Aquifer Layer using the Geoelectric Method in Teupin Batee Village, Aceh Besar - Syafrizal Idris; Dian Darisma; Agus Hari Pramana; Nurul Aflah; M Sayuti; Nanda Novita (Indonesian Scientific Journal, 2022)
The need for clean water around the world is related to the increasing population, especially in Teupin Batee Village, Aceh Besar District. In addition to surface water, groundwater is one of the potentials that can be utilized by the community, particularly for household needs. The purpose of this study is to identify the aquifer layer using the geoelectric method. One of the geophysical methods that can be used to map groundwater potential is the geoelectrical method based on the resistivity value of subsurface rocks. This study uses the Wenner-Schlumberger array because it can map subsurface structures both vertically and horizontally. From the results of the study, it was found that there are four different layers in this research area including, the top soil layer, hard rock, tuffaceous sand and sand layer as aquifer layer. The top soil layer is mixed with tuff, sand and volcanic breccia to a depth of 8 m with a resistivity value of 5-25 ?m. The Hard rock layer is at a depth of 8 m – 30 m with a resistivity value of 45-220 ?m. The tuffaceous sand layer has a resistivity value ranging from 25-55 ?m. While the sand layer or aquifer is at a depth of 10 m – 60 m with a resistivity value of <10 ?m which is separated by a layer of tuffaceous sand between the two aquifer layers.